Relationship between BMI with the Anthropometric Measurements and the Eating Habits of the Preclinical Medical Students of Universiti Kuala Lumpur Royal College of Medicine Perak (UniKL RCMP), Malaysia - ATM Emdadul Haque (Journal of Global Pharma Technology, 2017)
Background: In recent decades’ changes in Malaysians’ dietary habits and sedentary lifestyles due to the rapid acceleration of urbanization and industrialization leads to an increase in the prevalence of chronic diseases. BMI is used to calculate weight ranges from underweight to obese while an anthropometric measurement is a measurement for purposes of assessing growth and body fat distribution. Methods: This cross-sectional study was aimed at correlating BMI with the Anthropometric Measurements (AM) and the eating habit to see the trend of obesity and overweight. The study was done on the pre-clinical first and second-year medical students of UniKL RCMP. The study adopted a simple random sampling method on 172 students. A questionnaire was used, and BMI and AM were taken. Results: Students’ BMI revealed 18% underweight, 58.1% normal, 16.9% overweight and 7% obese. Although 38% students thought their eating habit was healthy, only 60% of students included all classes of the food pyramid in their daily meals and 95% did not even count their food calories. Moreover, 56% of students tend to eat more than usual when they became depressed. AM showed positive correlations between height and upper-arm-length; upper-arm-length and arm-circumference; arm-circumference and triceps-skinfold; triceps-skinfold and waist-circumference; triceps-skinfold and hip-circumference; and BMI and triceps skinfold. Conclusions: As various findings on eating habits had been discovered both supporting and contradictory, a more comprehensive study, if possible on all medical students would be helpful in finding out the actual prevalence of overweight and obesity among adolescents and providing more informative health education.Keywords: BMI, AM, Eating Habits, Medical Students, UniKL RCMP, Malaysia.